MORPHOLOGICAL, PHYSIOLOGICAL, AND IMMUNE RESPONSE OF NAKED NECK MALE CHICKENS FED CABBAGE LEAVES AS SELENIUM SOURCE REARED UNDER DIFFERENT PRODUCTION SYSTEMS - Urooj Khan; Jibran Hussain; Athar Mahmud; Anjum Khalique (Journal of Animal and Plant Sciences, 2026)
The experiment was designed to investigate the impact of cabbage leaves as a selenium source on the morphological, physiological, and immune responses of Naked-Neck male chickens raised under different production systems. For this, 96 Naked Neck cockerels (6 weeks old) were raised, and maintained at the Avian Research and Training (ART) Centre, UVAS, Ravi Campus, Pattoki. These experimental birds were allocated into 2 production systems (Intensive and free range) and 4 feeding strategies (control feed, 0.3mg per kg selenium from cabbage source, 0.3mg per kg selenium from sodium selenite source, and 0.3mg per kg selenium from cabbage + sodium selenite source). A factorial ANOVA was used to analyze the collected data, followed by a comparison of significant means through Duncan’s Multiple Range test. In the intensive production system, Naked Neck male birds exhibited greater morphometric traits and immune responses against Newcastle disease (ND) and Infectious Bronchitis (IB) compared to those reared in the free-range system; however, no difference was observed in the physiological response between the two systems. Regarding feeding strategies, greater morphometric traits, and immune responses against ND and IB were observed in birds reared on 0.3 mg per kg selenium from cabbage source feed treatment. On the other hand, higher bursa weight was found in those birds that were fed control feed and 0.3 mg per kg selenium from cabbage+ sodium selenite source-based feed treatment. Among physiological responses, higher heartbeat and respiratory rates were observed in birds raised on 0.3 mg per kg selenium from sodium selenite. Interactions between feeding strategies and housing systems showed significant variation among morphological, physiological, and immune responses. In conclusion, Naked Neck chickens exhibited excellent morphometric traits and a robust immune response when reared under an intensive production system supplemented with 0.3 mg per kg selenium from cabbage.
Keywords: Naked neck; morphometrics; immune response; production systems